FROM EXCLUSION TO BELONGING: IDENTITY FORMATION AND TRANSFORMATION IN WONDER (2017) THROUGH SOCIAL IDENTITY THEORY - Naomi Rebecca Sadia; Ayu Saraswati (ELite Journal : International Journal of Education, Language and Literature, 2026)
This study aims to examine the formation and transformation of August Pullman (Auggie) social identity as the main character in the American drama film Wonder (2017). Born with a facial difference caused by Treacher Collins Syndrome, Auggie experiences discrimination, exclusion, and bullying at school, which significantly influences his self-perception. The study applied a descriptive qualitative method with the film as the main data source, consisting of dialogues, monologues, and selected visual scenes. The visual data are analyzed by using narrative elements, including mise-en-scène and cinematography as the supporting data to strengthen the interpretation of social identity representation. The theory conducted by Tajfel and Turner (1979) includes the processes of social categorization, social identification, and social comparison. The findings show that Auggie is initially categorized based on his physical appearance, which leads to exclusion. This is reinforced through social identification, where peers adopt negative group norms, and social comparison, which positions Auggie as an out-group member. However, his social identity gradually changes through positive interactions, including developing friendships, moral reflection among classmates, reduced bullying, and supportive school experiences. Key turning points in the story lead to greater acceptance, confidence, and belonging. By the end of the movie, Auggie is recognized and accepted by his peers, showing personal growth and social change. Overall, this study concludes that social identity is dynamic and can change through positive interaction and acceptance within society.